Access to the internet and mobile applications in a mixed population emergency department: A repeated cross-sectional survey - Shannon Toohey; Michelle T. Nguyen; Soheil Saadat; Carrie E. Chandwani; Stephen F. Gassner; Alisa Wray; Ronald Rivera; Warren Wiechmann (PEC Innovation)
Objective: This study aimed to assess patients' interest in education content delivered through electronic modalities and identify trends in internet access and use among emergency department patients of various socioeconomic statuses. Methods: A prospective, cross-sectional survey with 50 questions was completed by 241 English and Spanish-speaking patients in 2014 and repeated with 253 participants in 2019 at the University of California, Irvine Medical Center's Emergency Department (UCIMCED). Results: Internet access increased from 83.8 % in 2014 to 88.1 % in 2019. Most internet-using patients owned smartphones (80.1 % in 2014, 89.7 % in 2019). Patients used electronic devices, such as fit bits and activity trackers, to obtain health information. Email was the preferred method for receiving discharge instructions. Conclusions: As of 2019, 88.1 % of UCIMCED patients have access to the internet or email, making electronic media a reasonable venue for patient education. Given that we have a predominantly low-income patient population—61 % and 32 % of respondents in 2014 and 2019, respectively, reporting an income of less than $25,000—these results are provide new avenues to reach patients of all socioeconomic statuses. Innovation: The implications of this study can be used to develop electronic resources tailored to educate emergency department patients about their healthcare beyond the confines of a hospital.